USING ENGLISH VOCABULARY GAMES TO DEVELOP VOCABULARY SPELLING AND RETENTION ABILITY OF MATTHAYOMSUKSA THREE STUDENTS - Intarasomjai, Nutdanai; U-nakarin, Tamronglak (Journal of Buddhist Education and Research (JBER), 2022)
The objectives of this research were to 1) compare the students’ vocabulary spelling and retention ability with criterion-referenced assessment (70 percent) 2) study the students’ opinions on English vocabulary games. The samples used in this research were 15 Matthayomsuksa Three students at Baan Bor Hoy School in the second semester of academic year 2020. The samples were chosen by purposive sampling. The instruments used in this study were lesson plans, an English vocabulary test and a questionnaire about the students’ opinions on English vocabulary games. The data were statistically analyzed by mean, standard deviation and t-test for one sample. The results were found that; 1) The students’ vocabulary spelling and retention ability were at high level. 2) The Matthayomsuksa Three students were satisfied with English vocabulary games.